2020
DOI: 10.7759/cureus.10070
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transfusion Transmissible Infections in Beta-Thalassemia Major Patients in Pakistan: A Systemic Review

Abstract: β-thalassemia major (TM) is one of the most prevalent inherited hemoglobinopathies in Pakistan. It has one of the highest prevalence of transfusion-dependent TM patients globally, with an estimated greater than 100,000 active cases. Blood transfusions (BT) are essential in the management of severe TM; it is critical to have a safe BT to reduce the risk of transfusion transmissible infections (TTIs). Frequent blood transfusions in these patients increase their risk of acquiring TTIs compared to the general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“… 34 , 39 In the current study, only one patient was positive for HIV. This is in accordance with other studies on HIV in this patient group in Pakistan 40 and indicates that luckily, for the time being, that HIV infection is not a health burden for thalassemia patients in Pakistan. This may be due to somewhat low prevalence rate of HIV infections in Pakistan.…”
Section: Discussionsupporting
confidence: 92%
“… 34 , 39 In the current study, only one patient was positive for HIV. This is in accordance with other studies on HIV in this patient group in Pakistan 40 and indicates that luckily, for the time being, that HIV infection is not a health burden for thalassemia patients in Pakistan. This may be due to somewhat low prevalence rate of HIV infections in Pakistan.…”
Section: Discussionsupporting
confidence: 92%
“…15 Among total number of thalassemia patients, the frequency of thalassemia in male was greater than female. We agreed with a study who observed that majority of thalassemia patients were males 16 . However studies found that gender differences in expression profiles of thalassemia patients proposing that females and males are differentially pretentious by the β thalassemia.…”
Section: Discussionsupporting
confidence: 91%
“…These numbers can be a real challenge for the health care system of a low and middle income country like Pakistan. 3 , 4…”
Section: Introductionmentioning
confidence: 99%